A DODGY QUESTION OF THE LEGAL FORM: FORMALITY REQUIREMENTS FOR THE POA GRANTED ABROAD TO ACT ON THE TERRITORY OF POLAND - Jaroslaw M. Szewczyk (European Scientific Journal, ESJ, 2014)
Ever increasing interest of foreign investors in establishing their businesses in Poland results in a build-up of problems concerning the legal form of taken actions. When it comes to acting and representing foreign entities before Polish authorities, including notaries, courts and public administrative bodies, the form of a power of attorney appears to be of a particular importance. The article deals with the issue of the due form of the power of attorney granted abroad to undertake actions on the territory of Poland. The author tries to address the most relevant problems relating to this issue, i.e. the issue of equivalence of forms, formal validity, application of an appropriate law and the legal power of legalisation and apostillisation of documents.